A Sociocultural Linguistic Analysis of Asexual Identity Construction in an Online Forum - Rosen, Sam (2023)
This thesis explores the construction of asexual identities by members of an online community of practice (the Asexual Visibility and Education Network, AVEN) which comes together around the discussion of asexuality. Data from an online ethnography and the distribution of a survey to community members have been analysed using discourse analysis and a sociocultural linguistic approach to explore the social contexts in which asexual identities are formed and the influence that they have upon the sorts of identity that community members can adopt. Using a theoretical framework which incorporates Bucholtz and Hall’s principles of identity (2005) and tactics of intersubjectivity (2004a, 2005), the community of practice model (Lave and Wenger, 1991) and queer linguistics, this thesis focuses upon the construction of individual identities, as well as that of the community of practice as a whole. It also looks at how the structure of the community influences the identities that individuals can claim and how these identities are negotiated between community members. I show that offering support and guidance, as well as engaging in debates about asexual topics, are important community practices which create a safe and productive environment for exploring asexual identities. Further, this thesis considers the way in which the community positions itself and asexuality in relation to the wider world; key to this is an investigation of the influence of allonormativity and issues of belonging and exclusion. I also look at the relevance of the community of practice model for understanding the online AVEN context.